1985
DOI: 10.1055/s-2007-999958
|View full text |Cite
|
Sign up to set email alerts
|

Beckwith-Wiedemann Syndrome: Prenatal Ultrasound Diagnosis Using Standard Kidney to Abdominal Circumference Ratio

Abstract: Enlarged fetal kidneys are characteristic of more than one possible diagnosis. Though infantile polycystic kidney disease is probably the most well known entity and is associated with oligohydramnios, Beckwith-Wiedemann syndrome should be considered in the differential diagnosis especially if a normal or increased amount of amniotic fluid is present. The presence of an omphalocele with a normal karyotype should also arouse suspicion. This constellation of findings carries potential morbidity including macrosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…While the majority of cases of BWS are diagnosed after birth on the basis of physical exam findings, fewer than 20 cases in the literature were diagnosed prenatally (Weinstein and Anderson, 1980;Shapiro et al, 1982;Nivelon-Chevallier et al, 1983;Grundy et al, 1985;Koontz et al, 1986;Winter et al, 1986;Cobellis et al, 1988;Lodeiro et al, 1989;Meizner et al, 1989;Wieacker et al, 1989;Shah and Metlay, 1990;Viljoen et al, 1991;Hewitt and Bankier, 1994;Nowotny et al, 1994;Whisson et al, 1994;Harker et al, 1997;Ranzini et al, 1997;Fert-Ferrer et al, 2000;Hamada et al, 2001). However, prenatal identification and diagnosis have become increasingly important in pregnancy counseling-in light of the burden of increased malignancy risk, large size, and the unusual phenotype; determining proper mode of delivery; managing potentially fatal neonatal issues, including airway obstruction, respiratory distress, hypoglycemia, and congestive heart failure (mortality as high as 21% (Pettenati et al, 1986)); and in counseling and testing family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of cases of BWS are diagnosed after birth on the basis of physical exam findings, fewer than 20 cases in the literature were diagnosed prenatally (Weinstein and Anderson, 1980;Shapiro et al, 1982;Nivelon-Chevallier et al, 1983;Grundy et al, 1985;Koontz et al, 1986;Winter et al, 1986;Cobellis et al, 1988;Lodeiro et al, 1989;Meizner et al, 1989;Wieacker et al, 1989;Shah and Metlay, 1990;Viljoen et al, 1991;Hewitt and Bankier, 1994;Nowotny et al, 1994;Whisson et al, 1994;Harker et al, 1997;Ranzini et al, 1997;Fert-Ferrer et al, 2000;Hamada et al, 2001). However, prenatal identification and diagnosis have become increasingly important in pregnancy counseling-in light of the burden of increased malignancy risk, large size, and the unusual phenotype; determining proper mode of delivery; managing potentially fatal neonatal issues, including airway obstruction, respiratory distress, hypoglycemia, and congestive heart failure (mortality as high as 21% (Pettenati et al, 1986)); and in counseling and testing family members.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that the prenatal diagnosis of BWS can be made in the mid-trimester of pregnancy by clinical findings of macrosomia, macroglossia, omphalocele, polyhydramnios, increased abdominal circumference, and renal or liver enlargement (Weinstein and Anderson, 1980;Grundy et al, 1985;Viljoen et al, 1991). A more recent report recommends using PCR of polymorphic loci on 11p15.5 to detect maternal deletions or inversions, paternal duplications, and uniparental disomy that may account for some cases of sporadic BWS (Reish et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…By using ultrasound equipment they noted increased amniotic fluid, bilateral cystic kidneys and a larger than expected fetus in a routine examination of a pregnancy at 20 weeks gestation. Carseldine et al [14] and Grundy et al [25] have described characteristic renal changes in WBS as judged by ultrasound examination. The final diagnosis of WBS was revealed at delivery.…”
Section: Prenatal Diagnosismentioning
confidence: 99%
“…Approximately 50% of the WBS patients were born before term ranging from 30 to 38 weeks [19]. Among the obstetric complications most frequently mentioned is hydramnios [25,93] which seems to occur in at least 50% of the pregnancies [19,35]. Possibly the prematurity is a function of increased fetal weight, whereas it is conceivable that the hydramnios reflects impaired swallowing due to macroglossia (cf below).…”
Section: Obstetrical Complicationsmentioning
confidence: 99%
“…Addition· al associated anomalies include renal, pancreatic islet cell, adrenocortical, and gonadal interstitial cell hy· perplasia, renal medullary dysplasia, facial nevus flammeus, ear lobe creases and mild microcephaly.t.3,5,1U6,17 Neonatal hypoglycemia, hemihypertrophy, and an increased predisposition to develop childhood embryonal neoplasms also are described frequently.1. [3][4][5]7,11,14,16 The prenatal diagnosis of BWS is important as it can alert both the obstetrician and the pediatrician to potential birth and perinatal complications. A 21% neonatal mortality rate has been reported as a result of dystocia, neonatal hypoglycemia, seizures, and cardiac failure.…”
Section: Discussionmentioning
confidence: 99%